The impact of blockchain technology on eco-labelling schemes: a study in the fishing industry - Cohen, Alexander (2020)
The food industry has an enormous global impact on the environment and our societies. With a broad variety of products available to us consumers, there is a rising demand for knowledge about the production of goods and their sustainability aspects. Eco-labels aim to provide credible information of where and how a food product was produced. Consumer confidence in eco-labels has decreased due to cases of inefficient auditing and fraudulent actors along the supply chain. New technologies such as blockchain could solve this issue. Blockchain is a public digitalised ledger, where all transactions are saved in a sequence of blocks. With its decentralized, fully traceable, transparent and auditable characteristics, blockchain technology has been proposed as a potential solution to improve supply chain governance. By analysing sustainable supply chain governance, eco-labelling schemes and blockchain technology implementation in the fishing industry, this thesis addresses how blockchain technology may impact eco-labelling schemes. It uses an exploratory qualitative approach to further define the field of research on blockchain applications for supply chain management and certification in the fishing industry, and to illustrate how key actors and processes may be affected by the introduction of blockchain technology. The paper concludes that blockchain technology alone does not create a substantial impact on certification processes in the fishing sector, as it does not prevent illegal, unregulated and unreported fishing, overexploitation of fish stock and mislabelling. This is mainly due to the physical link, which is needed to bridge physical and digital world. However, with a fully digitalized system in place, it can be a useful tool for managing supply chains effectively and provide increased transparency among supply chain actors. This paper is structured into five major sections: introduction, literature review, methodology, empirical findings and discussion.